Temperature dependence of helium-implantation-induced lattice swelling in polycrystalline tungsten: X-ray micro-diffraction and Eigenstrain modelling. (October 2015) - de Broglie, I.; Beck, C.E.; Liu, W.; Hofmann, F.
Abstract : Using synchrotron X-ray micro-diffraction and Eigenstrain analysis the distribution of lattice swelling near grain boundaries in helium-implanted polycrystalline tungsten is quantified. Samples heat-treated at up to 1473 K after implantation show less uniform lattice swelling that varies significantly from grain to grain compared to as-implanted samples. An increase in lattice swelling is found in the vicinity of some grain boundaries, even at depths beyond the implanted layer. These findings are discussed in terms of the evolution of helium-ion-implantation-induced defects.